2017
DOI: 10.7567/jjap.56.10pd06
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 〈110〉 grain-oriented 0.15BaTiO3–0.85(Bi0.5Na0.5)TiO3ceramics by a reactive templated grain growth method

Abstract: 〈110〉 grain-oriented ceramics with the composition of 0.15BaTiO3–0.85(Bi0.5Na0.5)TiO3 with a high Curie temperature of ∼300 °C were successfully fabricated by reactive templated grain growth of layered hydrogen titanate platelets with (Bi0.5Na0.5)TiO3 and BaCO3 matrix powders. A large degree of 〈110〉 orientation F110 = 84% was achieved by decreasing green sheet thickness and application of pressure on a compact during sintering. As a consequence, improved remanent polarization was observed in these ceramics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Moreover, the ceramics that presented large GS also featured large d 33 values. Nevertheless, the d 33 values of the ceramics in this study were very low compared with those reported by Ueno et al 9) Their ceramics exhibited high degree of orientation, which could have been the most probable reason for their high d 33 values. However, the relative density decreased.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…Moreover, the ceramics that presented large GS also featured large d 33 values. Nevertheless, the d 33 values of the ceramics in this study were very low compared with those reported by Ueno et al 9) Their ceramics exhibited high degree of orientation, which could have been the most probable reason for their high d 33 values. However, the relative density decreased.…”
Section: Resultscontrasting
confidence: 86%
“…The XRD patterns of the ceramics obtained using SPS presented the single BTBNT phase. Because the XRD patterns of BTBNT 9) were almost same as our obtained results. However, the peaks in the XRD pattern of the ceramics obtained using CV sintering separated at approximately 40°, which suggested the presence of mixed phase BT and BNT in the structure of these ceramics.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Sintering with weight-pressing could control the warpage associated with the oriented grains. 36) The warpage observed in the ceramics was controlled by pressing the debinded samples which was wrapped in platinum foil during sintering (WS). A crucible containing zirconia balls was used to impose a pressure of 17 kPa.…”
Section: Green and Sintered Ceramics Without The Uses Of A Weight-prementioning
confidence: 99%
“…32) With using the HTO template particles, ©110ª-oriented platelike BaTiO 3 particles, ©110ª-oriented 0.15BaTiO 3 0.85(Bi 0.5 Na 0.5 )TiO 3 ceramics, and ©100ª-oriented (Bi 0.5 Na 0.5 )TiO 3 ceramics have been successfully fabricated recently. 32),34), 36) In this study, we optimized various preparation conditions and successfully fabricated singleperovskite phase and highly textured BKT ceramics using HTO template particles by the RTGG method via a conventional sintering method.…”
Section: Introductionmentioning
confidence: 99%